Elevated expressions of survivin and VEGF protein are strong independent predictors of survival in advanced nasopharyngeal carcinoma - Yu‐Hong Li; Chun-Fang Hu; Qiong Shao; Ma-Yan Huang; Jing-Hui Hou; Dan Xie; Yi-Xin Zeng; Jian‐Yong Shao (2008)
Abstract Background Nasopharyngeal carcinoma (NPC) is one of the most common malignancies in southern China. The China 1992 TNM staging system has been widely used for prognosis prediction of NPC patients in China. Although NPC patients can be classified according to their clinical stage in this system, their prognosis may vary significantly. Method 280 cases of NPC with clinical follow-up data were collected and expressions of survivin and VEGF in tumor tissues were investigated by immunohistochemistry (IHC). Apoptosis index (AI) in 100 cases of NPC was detected by the TUNEL method. Results Expression of survivin and VEGF were significantly associated with TNM stage, T-stage and metastasis of NPC. The patients with survivin and VEGF over-expression presented lower 5-year survival rate, as compared to those of low-expression (42.32% vs. 70.54%, 40.1% vs. 67.8%, respectively, P < 0.05), especially in advanced stage patients (36.51% vs. 73.41%, 35.03% vs. 65.22%, respectively, P < 0.05). The 5-year survival rate in NPC patients with survivin and VEGF dual over-expression was significantly lower than that of patients with dual low-expression (18.22% vs. 73.54%, respectively; P = 0.0003). Multivariate analysis indicated that both survivin and VEGF over-expression in NPC tumor tissues were strong independent factors of poor prognosis in NPC patients. The mean AI in the 39 survivin low-expression cases was 144.7 ± 39.9, which was significantly higher than that in 61 survivin over-expression cases (111.6 ± 39.8) (T test, P < 0.05). Conclusion Survivin and VEGF over-expression are independent prognostic factors for the patients with NPC. These results also suggest that tumor survivin and VEGF expressions are valuable prognostic markers for prognosis prediction in NPC patients.